2017
DOI: 10.1177/0276236617749185
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Experiences Following Exposure to a Sham “God Helmet”: Evidence for Placebo, Individual Difference, and Time of Day Influences

Abstract: It has been claimed that applying weak complex electromagnetic patterns to the temporal lobes in a “God Helmet” stimulates the intrusion of right-hemispheric processes to awareness, resulting in exceptional experiences (ExEs). We explored the roles of wearing a sham helmet, time of day, and individual differences (paranormal belief, synesthesia, locus of control, hyperesthesia, and prior anomalous experiences) in alterations in consciousness and ExEs in the absence of neural stimulation. Thirty-two skeptics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…In an experimental study with undergraduates, Garrett and Cutting () observed that the pre‐existing paranormal beliefs of participants led them to find made‐up paranormal reports as scientific, believable, and credible. Simmonds‐Moore, Rice, O'Gwin, and Hopkins () applied weak complex electromagnetic patterns to the temporal lobes of 67 individuals to stimulate the intrusion of right‐hemispheric processes to awareness to explore the roles of paranormal belief and prior anomalous experiences. There were 32 skeptics and 35 paranormal believers.…”
mentioning
confidence: 99%
“…In an experimental study with undergraduates, Garrett and Cutting () observed that the pre‐existing paranormal beliefs of participants led them to find made‐up paranormal reports as scientific, believable, and credible. Simmonds‐Moore, Rice, O'Gwin, and Hopkins () applied weak complex electromagnetic patterns to the temporal lobes of 67 individuals to stimulate the intrusion of right‐hemispheric processes to awareness to explore the roles of paranormal belief and prior anomalous experiences. There were 32 skeptics and 35 paranormal believers.…”
mentioning
confidence: 99%